2019
DOI: 10.1186/s12943-019-0942-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel long noncoding RNA OTUD6B-AS1 indicates poor prognosis and inhibits clear cell renal cell carcinoma proliferation via the Wnt/β-catenin signaling pathway

Abstract: BackgroundThe long noncoding RNA (lncRNA) OTUD6B antisense RNA 1 (OTUD6B-AS1) is oriented in an antisense direction to the protein-coding gene OTUD6B on the opposite DNA strand. TCGA database data show that the expression of the lncRNA OTUD6B-AS1 is downregulated and that OTUD6B-AS1 acts as an antioncogene in a variety of tumors. However, the expression and biological functions of the lncRNA OTUD6B-AS1 are still unknown in tumors, including clear cell renal cell carcinoma (ccRCC).MethodsThe expression level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 38 publications
4
100
0
Order By: Relevance
“…It is significantly downregulated in systemic sclerosis skin biopsies (10). In the field of cancer research, Wang and colleague reported OTUD6B-AS1 was downregulated in ccRCC tissue samples, and that patients with low OTUD6B-AS1 expression had shorter overall survival than patients with high OTUD6B-AS1 expression, which showed that the different expression levels of OTUD6B-AS1 indirectly correlated with patient survival (11). We reported downregulation of lncRNA OTUD6B-AS1 in thyroid cancer.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…It is significantly downregulated in systemic sclerosis skin biopsies (10). In the field of cancer research, Wang and colleague reported OTUD6B-AS1 was downregulated in ccRCC tissue samples, and that patients with low OTUD6B-AS1 expression had shorter overall survival than patients with high OTUD6B-AS1 expression, which showed that the different expression levels of OTUD6B-AS1 indirectly correlated with patient survival (11). We reported downregulation of lncRNA OTUD6B-AS1 in thyroid cancer.…”
Section: Discussionmentioning
confidence: 65%
“…This study demonstrates that the lower expression of OTUD6B-AS1 is associated with poor prognosis of ccRCC (11). In vitro and in vivo evidence indicates that OTUD6B-AS1 functions as a tumor suppressor in ccRCC (11). However, the expressions and biological functions of OTUD6B-AS1 are still unknown in thyroid carcinomas.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…A number of studies have demonstrated that lncRNAs play a key role in the occurrence and development of different types of tumor (9)(10)(11). Studies have demonstrated that lncRNAs regulate several cancer characteristics, including cell proliferation, apoptosis and invasion (12)(13)(14). lncRNAs are highly valuable for determining the pathological characteristics of different types of tumor, analyzing the prognosis and providing appropriate treatment (15).…”
Section: Introductionmentioning
confidence: 99%